Entrepreneurial leadership behaviour among school principals: perspectives from Malaysian secondary school teachers - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh; Asimiran, Soaib (Universiti Putra Malaysia Press, 2014)
Entrepreneurial leadership is a particular leadership behaviour that enables leaders to face the challenges of their tasks and roles in the current environment of organisations. Education scholars believe that this type of leadership empowers educational leaders to meet the diverse needs of students as well as the ever-changing demands of the school environment. However, many questions have been raised on how to measure entrepreneurial leadership behaviour in educational settings and in particular among school principals. The main purpose of this study was to determine Malaysian secondary school principals' entrepreneurial leadership behaviour through teachers' perspectives using the Entrepreneurial Leadership Questionnaire. A total sample of 300 school teachers were asked to rate the frequency of entrepreneurial leadership behaviour in their school principals. The data was analysed using Structural Equation Modelling. The results indicated that the questionnaire is highly valid and reliable to measure school principals' entrepreneurial leadership behaviour. Furthermore, entrepreneurial leadership is a multi-dimensional construct that can be explained by five leadership behaviours including general entrepreneurial leader behaviour, explorer behaviour, miner behaviour, accelerator behaviour and integrator behaviour. Implications of the findings are also discussed in this paper.